The new public governance? Emerging perspective on the theory and practice of public governance - Osborne, Stephen páginas
Despite predictions that new public management would establish itself as the new paradigm of Public Administration and Management, recent academic research has highlighted concerns about the intra-organizational focus and limitations of this approach. This book represents a comprehensive analysis of the state of the art of public management, examining and framing the debate in this important area